A conceptual model for mental health and performance of North American athletes: A mixed methods study. (July 2022) - Ayala, Erin; Nelson, Laina; Bartholomew, Matthew; Plummer, David
Abstract: Objective: The demands of sport create psychological and physical challenges for athletes, making it essential to understand what factors contribute to mental health and performance optimization in sport. The purpose of this mixed-methods investigation was to develop a conceptual model for mental health and performance of North American athletes. Method: Forty-three experienced athletes, coaches, and sport professionals identified, sorted, and rated 113 behaviors, thoughts, and feelings that contribute to optimal mental health and performance for athletes. Using Multidimensional Scaling, the research team created a two-dimensional point map of participant responses. Hierarchical Cluster Analysis was then used to reveal underlying clusters in the data. Findings: Seven clusters emerged from the data: Stress Management, Mental Skills, Self-Awareness, Managing Setbacks, Intentional Practice, Team Relationships, and Social Support. Though all clusters were rated as important to mental health and/or performance, the Managing Setbacks cluster displayed high importance ratings for both mental health and performance. Conclusion: Our preliminary findings suggest a comprehensive approach to athlete thoughts, feelings, and behaviors contributes to optimal mental health and performance for North American athletes. Highlights: Seven clusters contributed to optimal wellness and performance for North American athletes. We used mixed methods to capture views of athletes, coaches, and sport professionals. The conceptual model reflects a balanced approach to sport that combines psychological, physiological, and social factors.